2011
DOI: 10.1016/j.alcohol.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in extracellular levels of glutamate in the nucleus accumbens after ethanol-induced behavioral sensitization in adolescent and adult mice

Abstract: Repeated administration of low doses of ethanol gradually increases locomotor responses to ethanol in adult Swiss mice. This phenomenon is known as behavioral sensitization. However, we have shown that adolescent Swiss mice show either behavioral tolerance or no sensitization after repeated ethanol injections. Although the mesolimbic dopamine system has been extensively implicated in behavioral sensitization, several studies have demonstrated an important role of glutamatergic transmission in this phenomenon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 48 publications
6
21
2
2
Order By: Relevance
“…Our results revealed no differences in BECs between postweanling, adolescent, and adult mice, regardless of the tested dose, whereas there were statistically significant behavioral differences. These results, in agreement with previous studies (Carrara-Nascimento et al 2011;Faria et al 2008;Stevenson et al 2008), confirm that pharmacokinetic factors do not account for the age-related differences in ethanol-induced locomotor sensitization.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results revealed no differences in BECs between postweanling, adolescent, and adult mice, regardless of the tested dose, whereas there were statistically significant behavioral differences. These results, in agreement with previous studies (Carrara-Nascimento et al 2011;Faria et al 2008;Stevenson et al 2008), confirm that pharmacokinetic factors do not account for the age-related differences in ethanol-induced locomotor sensitization.…”
Section: Discussionsupporting
confidence: 94%
“…Based on such results, previous studies concluded that adolescent mice are less sensitive to ethanol sensitization (Carrara-Nascimento et al 2011;Stevenson et al 2008) or globally develop behavioral tolerance to the stimulant effects of ethanol (Camarini et al 2010;Faria et al 2008). However, in order to have a full picture of ethanol-induced sensitization in adolescent mice, the present study also tested higher ethanol doses (3.5 and 4 g/kg).…”
Section: Discussionmentioning
confidence: 79%
“…Consequently, such experiences might acquire a special character because the adolescents might repeat them several times. This hypothesis seems to agree with some findings reported in the literature that show that DA release in the reward system in adolescent rats is greater when they are exposed to new situations [36] or given cocaine [37], methamphetamine [38], or alcohol [39,40].…”
Section: Introductionsupporting
confidence: 87%
“…Furthermore, because we targeted the medial NAcc, the sub-region that projects predominantly to VTA, we believe that the effects we observed may involve mGlu7 receptors in the VTA. We interpret our results to suggest that ethanol-induced increase in extracellular glutamate can activate mGluR7 in NAcc projection fibers to the VTA (Carrara-Nascimento et al, 2011;Melendez et al, 2005;Piepponen et al, 2002;Xiao et al, 2009) This would enhance the sensitivity to the stimulant and rewarding effects of ethanol, although the possibility of relevant actions in other regions that receive projections from NAcc (eg, the ventral pallidum) (Hubert et al, 2011;Li et al, 2009;Maurice et al, 1998;Sharp et al, 2010) cannot be excluded. Both dopamine and glutamate levels increase significantly in the NAcc following ethanol administration Imperato, 1985, 1986;Imperato and Di Chiara, 1986;Siggins et al, 2003;Yan et al, 1998).…”
Section: Discussionmentioning
confidence: 81%